Methods of Anti-Corruption Education According to Sheikh Al-Usaimin's Perspective - Sinaga, Sopian (MODELING: Jurnal Program Studi PGMI, 2024)
Corruption has become a common thing we hear everyday, as if it has become a culture that will continue to exist in society. Various efforts have been made by the government to eliminate this disease, but it seems that the drugs given are only painkillers, not disease removers, that's why the disease has not disappeared until now, even tends to get bigger. This research uses qualitative research methods with the type of library research, the data comes from related literature that is relevant to the anti-corruption education method in the perspective of Sheikh Al-Usaimin. The results of this study indicate that Sheikh Al-Usaimin's concept includes direction to school principals, teachers and students. The three of them must go hand in hand together. Leaders and teachers provide examples and role models to students, namely in practicing Islamic teachings, including in terms of devotion, being qanaah and staying away from extravagant attitudes or hedonism styles. Leaders apply rules, control and supervise as well as provide guidance and direction. Teachers instill noble values in learners. Learners follow the direction of the school, namely increasing devotion, always feeling with Allah and the Prophet, always being qanaah, maintaining authority and honor, staying away from a luxurious lifestyle, inviting people to practice Islamic teachings.